519 Restless Legs and Periodic Limb Movements in 86 patients with Multiple Sclerosis. (3rd May 2021) - Sparasci, Davide; Ferri, Raffaele; Castelnovo, Anna; Gobbi, Claudio; Zecca, Chiara; Riccitelli, Gianna; Disanto, Giulio; Carelli, Chiara; Miano, Silvia; Tanioka, Kosuke; Tachibana, Naoko; Manconi, Mauro
Abstract: Introduction: The aim of this study was to assess the prevalence of restless legs syndrome (RLS), periodic limb movements during sleep (PLMS) and their overlap in a large population of patients with multiple sclerosis (MS), and to compare clinical and paraclinical findings between patients with and without RLS/PLMS. Methods: In this cross–sectional, observational, instrumental study, eighty-six patients (M/F: 27/59; mean age 48.0 ± 10.8 years) with a diagnosis of MS underwent a structured telephone interview assessing the five standard diagnostic criteria for RLS. Seventy-six participants underwent Video-polysomnography and Maintenance of Wakefulness Test (MWT). Instrumental and clinical findings were subsequently statistically compared to investigate their association with RLS and PLMS index (PLMSI). Results: RLS and PLMS (PLMSI ≥15/h) prevalence in patients with MS was of 31.4% and 31.6% respectively. Among patients with RLS, 37.5% had a PLMSI ≥15/h. In the group with PLMS, 37.5% met all diagnostic criteria for RLS. No differences were found between patients with and without RLS (F = 0.99, p = 0.45), and between patients with and without a PLMSI ≥15/hour (F = 0.32 p = 0.94) on the pool of clinical and instrumental variables. Conclusion: RLS is highly prevalent and severe in patients with MS. The prevalence of PLMS is comparable to the general population. The low percentage of patients with RLS having a high PLMSI, together with the absence of correlation between RLS and female gender and older age, support the existence of a distinct symptomatic form of RLS in MS. Support (if any):